The Application Of Islamic Business Ethics For Inclusive Students In The Perspective Of The Qur'an In Senior High School 6 Muhammadiyah Surakarta - Sulistianingrum, Sekar; Istanto (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This research aims to analyze, explain, and describe how the application of Islamic business ethics in the perspective of the Qur'an can provide a strong moral foundation for the inclusion of students in running their businesses. It helps them become responsible and ethical business leaders in society. This observation or research uses a descriptive qualitative approach method. The research technique is carried out in the form of data collection through observation, interview, and documentation methods. The results of the research can be described as follows based on the explanation of the theoretical study, the results of the research, and the analysis, which was previously carried out by the author at SMA Muhammadiyah 6 Surakarta. The author can draw conclusions and analysis from the Implementation of Islamic Business Ethics from the Perspective of the Qur'an at SMA Muhammadiyah 6 Surakarta that the implementation of Islamic business ethics from the perspective of the Qur'an can help inclusion students build businesses that are not only materially successful but also reflect high moral and ethical values. By understanding and applying Quranic principles in their business, inclusion students can contribute positively to the business world while following their religious teachings.